Efektifitas Metode Pengukuran Perilaku Seksual Remaja Usia 15-21 Tahun Berdasarkan Teknik Self Administered dan Interview-Based Questioner - Sri Rahayu Sanusi; Lanova Dwi Arde M. (Politeknik Kesehatan Tanjung Karang, 2019)
The result of the Population Census shows about 41 million or 26% of the Indonesian population are adolescents aged 10-24 years. It will cause many problems, such as sexual behaviors. Sexual health problem is a sensitive issue that is both privacy and at the same time regulated by social and religious norms. This is one of the causes of getting a true number of young people's sexual behavior was difficult. So, we did a study to compare the effectiveness of self-administered and interview-based questioner methods to obtain a true number of young people's sexual behavior. It was a comparative-quantitative study, using 360 students of SMK X and Faculty of Y in Medan City age 15-21 years as samples, gotten by simple random. This study showed that using a self-administered method, young people reported they got intercourse when they were with boy/girlfriend about 7,9%, and using interview-based questioner method 5,0%. Young people who reported that ever got intercourse in a self-administered method about 8,6%, and using interview-based questioner method 3,3%. The result showed there is different reporting young people’s sexual behavior between self-administered method and interview-based questioner method. Young people were more likely to report sexual behaviors by self-administered method compared to interview-based questioner method.